Initial experience of ureteric visualization using methylene blue during laparoscopy for gynecological surgery - Shao, Ruyu; Shen, Faquan; Soleymani majd, Hooman; Qin, Xiaoqing; Yao, Desheng; Long, Ying; Wang, He; Wei, Yousheng; Chang, Xin (Frontiers in Surgery, 2024)
Objective: Iatrogenic ureteral injury is a significant complication in gynecological laparoscopic surgeries, with incidence rates reaching 1.5%. This report documents our initial experience using methylene blue (MB) for ureteral visualization and explores its effectiveness and safety. Additionally, we introduce the simultaneous visualization of ureteral MB fluorescence and sentinel lymph nodes (SLNs) using the same camera system. Methods: This study included patients undergoing gynecological laparoscopic procedures performed by the same surgeon. MB was rapidly infused intravenously at the outset of surgery. For cases requiring SLN imaging, ICG was injected into the cervix. Cases were evaluated intraoperatively and postoperatively, comparing those with MB fluorescence (Group A) to controls without (Group B). Results: Among 25 patients (Group A) receiving MB, 45 ureters were clearly visualized, achieving a 90% imaging success rate. Continuous, clearer fluorescence imaging was observed in cases of ureteral hydronephrosis. Most patients showed ureteral fluorescence 15-20 minutes post-MB infusion, with 64% still fluorescing at surgery's end. Dual fluorescence imaging with ICG and MB was successful. No iatrogenic ureteral injuries occurred in the MB group (0%), contrasting with 1.3% in controls. Adverse events rates were similar between groups. Conclusion: MB fluorescence effectively and safely visualizes ureters in gynecological laparoscopic surgery, potentially reducing iatrogenic injuries without increased adverse effects. This technique shows promise for clinical application.